2014
DOI: 10.1021/ol5005438
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Oxidation Reactions Catalyzed by a Mononuclear Non-heme Iron Enzyme (OvoA) in Ovothiol Biosynthesis

Abstract: OvoA in ovothiol biosynthesis is a mononuclear non-heme iron enzyme catalyzing the oxidative coupling between histidine and cysteine. It can also catalyze the oxidative coupling between hercynine and cysteine, yet with a different regio-selectivity. Due to the potential application of this reaction for industrial ergothioneine production, in this study, we systematically characterized OvoA by a combination of three different assays. Our studies revealed that OvoA can also catalyze the oxidation of cysteine to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 44 publications
(109 reference statements)
3
84
1
Order By: Relevance
“…When fed an HID, both wild‐type and Slc7a11 –/– mice develop severe tissue iron overload, and serum transferrin binding approaches saturation (http://onlinelibrary.wiley.com/doi/10.1002/hep.29117/suppinfo), suggesting the presence of non‐transferrin‐bound iron in the circulation. Circulating non‐transferrin‐bound iron depletes GSH and oxidizes cysteine to form cysteine, which can then be imported into cells through the Slc7a11 transporter. Consistent with this process, we found increased levels of Slc7a11 mRNA in iron‐overloaded wild‐type mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When fed an HID, both wild‐type and Slc7a11 –/– mice develop severe tissue iron overload, and serum transferrin binding approaches saturation (http://onlinelibrary.wiley.com/doi/10.1002/hep.29117/suppinfo), suggesting the presence of non‐transferrin‐bound iron in the circulation. Circulating non‐transferrin‐bound iron depletes GSH and oxidizes cysteine to form cysteine, which can then be imported into cells through the Slc7a11 transporter. Consistent with this process, we found increased levels of Slc7a11 mRNA in iron‐overloaded wild‐type mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4d). Hints of mechanistic similarities between EgtB/OvoA and CDO existed prior to the report of the crystal structure, such as the observation that OvoA incubated with hercynine (the normal substrate for EgtB oxidation) and cysteine produces primarily CSA, the product of CDO-type chemistry[97]. Thus it seems that the reactive oxygen species is poised to effect dioxygenation of sulfur in OvoA if the sulfur is not precisely oriented for addition to the imidazole ring.…”
Section: Sulfoxide-synthases: Egtb and Ovoamentioning
confidence: 99%
“…Thus it seems that the reactive oxygen species is poised to effect dioxygenation of sulfur in OvoA if the sulfur is not precisely oriented for addition to the imidazole ring. More careful reexamination revealed that, even when OvoA was incubated with its native substrates (L-Cys and L-His), approximately 10% of the cysteine is converted to CSA [97]. Very recently, the structural insights gleaned from the EgtB crystal structure were used to assess the importance of various active site residues [98].…”
Section: Sulfoxide-synthases: Egtb and Ovoamentioning
confidence: 99%
“…These enzymes perform different reactions, including sulfur oxidation (IPNS) and sulfur oxygenation (CDO, ETHE1). 812 …”
Section: Introductionmentioning
confidence: 99%